2014
DOI: 10.1038/srep07483
|View full text |Cite
|
Sign up to set email alerts
|

How is water-use efficiency of terrestrial ecosystems distributed and changing on Earth?

Abstract: A better understanding of ecosystem water-use efficiency (WUE) will help us improve ecosystem management for mitigation as well as adaption to global hydrological change. Here, long-term flux tower observations of productivity and evapotranspiration allow us to detect a consistent latitudinal trend in WUE, rising from the subtropics to the northern high-latitudes. The trend peaks at approximately 51°N, and then declines toward higher latitudes. These ground-based observations are consistent with global-scale e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 36 publications
10
149
3
2
Order By: Relevance
“…Currently, NASA TERRA and AQUA MODIS-based estimates of GPP and ET have been developed and improved greatly during the past decade which can also be obtained to quantify large-scale WUE (Lu and Zhuang, 2010;Tang et al, 2014). Zhao et al (2005) rectified the GPP products by improving the data processing methods and modifying parameters in the algorithm used, which generated the improved Collection 5 MOD17 estimates.…”
Section: Modis Products and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, NASA TERRA and AQUA MODIS-based estimates of GPP and ET have been developed and improved greatly during the past decade which can also be obtained to quantify large-scale WUE (Lu and Zhuang, 2010;Tang et al, 2014). Zhao et al (2005) rectified the GPP products by improving the data processing methods and modifying parameters in the algorithm used, which generated the improved Collection 5 MOD17 estimates.…”
Section: Modis Products and Processingmentioning
confidence: 99%
“…By combining these fluxes with satellite-based remote sensing, it has become possible to upscale the spatiotemporal variability of land-surface exchanges at regional to global scales (Zhao et al, 2005;Jung et al, 2010;Tang et al, 2012). Although Tang et al (2014) using MODIS products on annual time scale, the consistencies with tower-based WUE at short time scales remain unclear. Meanwhile, it is important to understand how management practices affect the agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Field studies have also reported on the mixture effects caused by BL and NL PFTs on both the SWC and productivity (Falge et al 2002;Pretzsch et al 2015;Tang et al 2014). However, the assumption of complete soil water mixing can result in erroneous flux estimation (Hartmann 2016;Rihani et al 2010;Wagener and Gupta 2005).…”
Section: Effects Of Sub-surface Soil Water Mixing On Carbon Flux Estimentioning
confidence: 99%
“…Carbon and water cycles are closely related in the terrestrial ecosystem because the exchange of carbon dioxide and water vapor between the biosphere and atmosphere are both controlled by stomata (Beer et al 2009). Water use efficiency (WUE), the ratio of gross primary productivity (GPP) to evapotranspiration (ET), can be used to quantify this coupling relationship (Yu et al 2004;Tang et al 2014;Wang et al 2015;Zhu et al 2015). A better understanding of WUE will provide an alternative approach for carbon budget assessment (Beer et al 2007(Beer et al , 2010.…”
Section: Introductionmentioning
confidence: 99%